Implementação da metodologia de cuidados Humanitude - Melo, Rosa Cândida de Carvalho Pereira de (2016)
Objectives: To implement Humanitude Care Metodology in the context the teaching and care practice. Relevance and impact of the project Training nursing students in Clinical Practice to develop skills of relationship and communication through the appropriation of Humanitude Care Methodology; Implementation and dissemination of Humanitude Care Methodology in care units; Creating a reference framework for humanized care, evaluation of its effectiveness and accreditation. Productivity/Main Achievements Organization of International Conferences and workshop Education course in Humanitude lectured to the ESEnfC teachers 7 oral scientific presentations in international health congresses with abstracts published on indexed journals 5 book publications